Low-profile, Broadband Polarization Converting Surface Ground Planes for Antenna Polarization Diversity - Lail , Brian A.; Han, Kyu Y. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A broadband antenna backed by a polarization converting surface ground plane is presented. The conversion of reflected field polarization provides diversity from a single, linearly polarized antenna, while avoiding broadside nulls in the radiation pattern as a function of frequency. Results for a low-profile dipole planar inverted cone antenna ?/10 above a polarization converting surface indicate greater than 40% bandwidth. Comparison with solid ground planes and high impedance ground planes are discussed, with polarization diversity and lack of broadside nulls identified as key advantages to the proposed design.